Misunderstandings about developmental dyslexia: a historical overview - Pietro Smirni; Luigi Vetri; Eliana Misuraca; Marco Cappadonna; Francesca Felicia Operto; Grazia Maria Giovanna Pastorino; Rosa Marotta (MDPI AG, 2020)
History of the reading disorder not due to an intellectual disability, inadequate teaching systems or poor motivation to study, referred to as developmental dyslexia, has very remote origins. The first attempts explain the disorder as a primary 'visual defect'. Since then, several models have been developed until autopsy and histo-pathological studies on the brains of developmental dyslexics provided neuroanatomical evidence on the structural and morphologic differences between normal and dyslexic brains. In addition, the new neuroimaging technologies have allowed to understand the neural systems of reading and dyslexia. According to recent studies, developmental dyslexia appears as a neurodevelopmental multicomponent language-related disorder with a deficit in phonological decoding and in visuospatial organization of linguistic code. As a result, rehabilitation must be focused on the recovery of language and visuo-spatial and attentional processes underlying the complex and multi-component developmental dyslexia. This brief overview should be a valid tool for a deeper understanding of the dyslexic disorder. Literature searches in Medline, PsycINFO, EMBASE, Scopus, PubMed, Web of Science identified one hundred articles focusing attention on how this disorder has been considered over the years.